Benign recurrent intrahepatic cholestasis (BRIC): Is it really as benign as anticipated? - (:unkn) unknown (My University, 2003)
We report an 18 year old male patient with a known diagnosis of BRIC who presented with acute renal failure secondary to hyperbilirubinemia in three successive episodes. Renal replacement therapy was required in all three episodes but his renal function recovered to baseline creatinine on discharge. Proposed pathophysiology of ARF in the setting of hyperbilirubinemia includes direct tubulotoxicity and sequestration of pigment casts within the tubular lumen causing tubular obstruction aggravated by dehydration. We emphasize the importance of vigorous hydration to be started with the impending attack to prevent progression to ARF.
Keywords: Acute Renal Failure; BRIC